2021
DOI: 10.1186/s12872-021-02123-1
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant acute myocardial infarction and acute pulmonary embolism caused by paradoxical embolism: a case report

Abstract: Background Due to its low incidence and diverse manifestations, paradoxical embolism (PDE) is still under-reported and is not routinely considered in differential diagnoses. Concomitant acute myocardial infarction (AMI) and acute pulmonary embolism (PE) caused by PDE has rarely been reported. Case presentation A 45-year-old woman presented with acute chest pain and difficulty with breathing. Multiple imaging modules including ECG, echocardiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The diagnosis of MINOCA should be made in the absence of obstructive (lesion ≥ 50%) coronary artery disease. Coronary artery spasm (CAS) syndrome, coronary dissection, in situ thrombosis [ 3 ], tachycardia, and coronary embolism [ 4 ] are all etiologies that can cause MINOCA. The careful collection of medical history, and specialized examinations such as intracoronary imaging or the ergonovine provocation test, can facilitate the differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of MINOCA should be made in the absence of obstructive (lesion ≥ 50%) coronary artery disease. Coronary artery spasm (CAS) syndrome, coronary dissection, in situ thrombosis [ 3 ], tachycardia, and coronary embolism [ 4 ] are all etiologies that can cause MINOCA. The careful collection of medical history, and specialized examinations such as intracoronary imaging or the ergonovine provocation test, can facilitate the differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis revealed that 34.3% of patients with PE showed ST-segment elevation in the aVR, which must be differentiated from LM or 3-vessel ACS [ 16 ]. Furthermore, reports in the literature indicate that ST-segment elevation in patients with PE can also result from coronary artery embolism secondary to a patent foramen ovale; in such cases, both PE and coronary embolism coexist, leading to ECG changes that reflect the combined effects of these two conditions [ 17 , 18 ]. Certain ECG features associated with PE can predict a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…There have been multiple reports of patients dying from a fatal coronary artery occlusion due to a paradoxical embolism traveling through interatrial communication [ 18 , 19 ]. Additionally, there have been cases of individuals with a PFO who have simultaneous MI from paradoxical emboli and a pulmonary embolism [ 20 , 21 ]. In such patients, it is of even greater importance to discriminate the causes of their symptoms so that the PFO and paradoxical embolism are not missed in the setting of a massive pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%